2020
DOI: 10.1155/2020/4976238
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Load Bearing Characteristics of Steel Fiber Reinforced Concrete Lining in the Soft Surrounding Rock Tunnel

Abstract: Tunnels in soft rock with high ground stress will encounter the problem of large deformation of surrounding rock. The study of new high-performance tunnel lining materials is of great significance to improve the safety of tunnel excavation in soft rock with high ground stress. In this paper, the bearing characteristics of the plain concrete, the reinforced concrete, and the steel fiber reinforced concrete lining are studied by the indoor model experiment. By extracting the displacement and stress data of typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…e quality of the latter directly affects the detection results, and it is likely to be affected by external factors such as uneven illumination and distortion of line-array camera shooting [2]. erefore, for these two methods, the accuracy of detection completely depends on the professional level and quality of technical personnel, and the measurement results of different personnel are not the same.…”
Section: Introductionmentioning
confidence: 99%
“…e quality of the latter directly affects the detection results, and it is likely to be affected by external factors such as uneven illumination and distortion of line-array camera shooting [2]. erefore, for these two methods, the accuracy of detection completely depends on the professional level and quality of technical personnel, and the measurement results of different personnel are not the same.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between the physical and similar materials of surrounding rock and the physical and mechanical parameters of the class IV surrounding rock [43] is shown in Table 9. Based on the successful test experience of existing research [49,50], the steel fiber was simulated using experimental ultra-fine steel fiber to carry out the relevant model test, as shown in Figure 7. The content of steel fiber was determined according to the recommended content for steel fiber identified in the second chapter.…”
Section: Similar Materialsmentioning
confidence: 99%
“…High-performance concrete materials have been studied, but there are still a limited number of studies on the use of these materials in the lining supports of the surrounding rocks in underground engineering projects. Through laboratory model tests, Cui et al [13] found that after becoming deformed, the initial support of steel-fiber concrete may intersect with the characteristic curve of the surrounding rock, thereby enabling the surrounding rock structure to remain stable. Guo [14] studied the concrete used for grouting reinforcement, compared the setting times of phosphoric acid-water glass and cement-water glass with different mix ratios, and proposed relevant design parameters.…”
Section: Introductionmentioning
confidence: 99%